Plate No. 12: Medicinal Plants - Lyman, Henry M. (Henry Munson) (The Book of Health, 1898)
Depicts mullein, rosemary, nettle, and deadly nightshade.
Keywords: Rosemary; Medicine; Medicinal plants; Mulleins; Medicine, Popular; Belladonna (Plant); Nettles